EFFECT OF CRUDE EXTRACT FROM MARINE POLYCHEATE CAPITELLA CAPITATA ON LARVAL SETTLEMENT OF BALANUS AMPHITRITE (CIRRIPEDIA, CRUSTACEA) - JADHAV S. S. (International Journal of Pharma and Bio Sciences, 2015)
Marine biofouling is a serious problem caused by the accumulation and settlement of microbial slimes, diatoms, barnacles, tunicates, bryozoans etc., on the hulls of seafaring vessels. In the present study, an attempt has been made to investigate the antifouling potential of marine Polycheates interaction against the settlement of cyprid larvae of B. amphitrite. The crude extract of Polycheate Capitella capitata significantly inhibited the cyprid larval settlement (P<0.5) than the control. The EC50 value of the crude extract (8 mg/ml) was lower than all the fractions. At higher concentration (16mg/ml), the crude extract of Polycheate Capitella capitata strongly inhibited the larval settlement